Formation of novel amino vic-dioxime complexes of Cu(II), Ni(II), Co(II) and Cd(II) of 1,3- Dioxalane groups containing the oxime moiety: Thermal, magnetic and spectral studies - Duman, Sibel; Sekerci, Memet (My University, 2012)
A novel substituted vic-dioxime ligand containing the amino group, N,N-[2,2-{ethane- 1,2-di-yl-bis(oxy)bis(2,1-phenylene)}bis(N-hydroxy)-2- (hydroxyimino)acetimidamide] (L1) has been prepared from 1,2-bis(o-aminophenoxy) ethane, anti-chloroglyoxime. The new complexes derived from L1 with Cu(II), Ni(II), Co(II) and Cd(II) complexes of 6,7-O-Cyclopentlydine-1- amino-4-azaheptane (L2) have been reacted at 60-65 °C temperature. The ligand1:metal:ligand2 ratio of these complexes have been found to be 1:2:2. The new Cu(II), Ni(II), Co(II) and Cd(II) complexes of these ligands are proposed to be octahedral. These new complexes have been characterized by elemental analyses, molar conductivity, magnetic susceptibility, IR, 1H-NMR, UVVis spectra and TGA techniques.
Keywords: Amine; Transition metal complexes; Vic-dioxime